The Problematic Nature of Marriage Dispensation from the Perspective of Maqāṣid al-Sharī‘ah - Hasanudin; Moh. Jeweherul Kalamiah (PT. Education Research Center, 2025)
This study examines the problematics of marriage dispensation from the perspective of Islamic law grounded in maqāṣid al-sharī‘ah, as well as Indonesia’s positive law following the enactment of Law No. 16 of 2019, which revised the minimum legal age for marriage. The primary focus of the study lies in a conceptual analysis of marital readiness based on two key indicators: baligh (physical maturity) and rusyd (intellectual and emotional maturity), along with an evaluation of the implementation of marriage dispensation in religious courts within the framework of child protection. The research employs a qualitative method based on library research and adopts a normative-juridical approach that integrates Islamic legal analysis with national legal norms. The findings reveal that under Islamic law, marriage dispensation is justified only under ḍarūrah (emergency) conditions aimed at securing public benefit (maṣlaḥah) and preventing harm (mafsadah), in line with the principles of maqāṣid al-sharī‘ah, particularly the protection of life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), and lineage (ḥifẓ al-nasl). However, in practice, the assessment of psychological and social readiness of prospective brides and grooms is often inadequate, and the strong influence of patriarchal culture contributes to the frequent misuse of dispensations. This situation reflects a contradiction between the ideal norms of law and the realities of social practice. Therefore, synergy between the values of Islamic law and the national legal system is crucial to ensure comprehensive child protection, achieve substantive justice, and strengthen maqāṣid as an ethical and moral foundation in the enforcement of Islamic family law in Indonesia.